2020
DOI: 10.3892/etm.2020.9116
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy dysfunction may be involved in the pathogenesis of ankylosing spondylitis

Abstract: The present study aimed to investigate the expression and significance of the mRNA of genes associated with autophagy and long non-coding RNA (lncRNA) GAS5 in peripheral blood mononuclear cells (PBMCs) of patients with ankylosing spondylitis (AS). The mRNA levels of microtubule-associated protein light chain 3 (LC3), Beclin1, autophagy-related gene (ATG)3, ATG5, ATG12, ATG 16 ligand 1 (ATG16L1) and lncRNA growth arrest-specific 5 (GAS5) in PBMCs from 60 patients with AS and 30 healthy controls (HC) were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In contrast, the findings from the team of Rik Lories support the downregulation of autophagy-related genes (ATG16L1, IRGM, HSP90AA1) in PB ( 161 ). Further research revealed autophagy dysfunction with the downregulation of MAP1LC3A and ATG5/12/16L1 in PBMCs, covering all markers used in the previous study ( 162 ). This dysfunction is attributed to a decrease in the autophagy mediator lncRNA GAS5.…”
Section: Hla-b27 Tuned Immunitymentioning
confidence: 63%
“…In contrast, the findings from the team of Rik Lories support the downregulation of autophagy-related genes (ATG16L1, IRGM, HSP90AA1) in PB ( 161 ). Further research revealed autophagy dysfunction with the downregulation of MAP1LC3A and ATG5/12/16L1 in PBMCs, covering all markers used in the previous study ( 162 ). This dysfunction is attributed to a decrease in the autophagy mediator lncRNA GAS5.…”
Section: Hla-b27 Tuned Immunitymentioning
confidence: 63%
“…For example, Li et al reported that the expression of lncRNA MEG 3 was downregulated in AS (19), which affected the length of the patient's hospital stay. Tan et al proposed that the pathogenesis of AS might be related to insufficient autophagy and downregulation of lncRNA GAS 5, and lncRNA GAS 5 might have clinical application value (20). Our discovery gives a new hint of uncovering the traits of AS and exploiting a prospective target for AS treatment.…”
Section: Discussionmentioning
confidence: 81%
“…SNHG16 is related to MAPK1 , which is one of the key genes in ferroptosis; SNHG16 is also involved in intracerebral hemorrhage [ 103 ]. GAS5 has been described in both an AS cross-sectional study and a ferroptosis-related bioinformatics study [ 104 , 105 ]. Because these non-coding RNAs are simultaneously associated with redox homeostasis and musculoskeletal disorders, they may be bridging molecules between ferroptosis and AS, and may, therefore, be possible therapeutic targets and tools in future research.…”
Section: Discussionmentioning
confidence: 99%